PENGARUH LATIHAN DRILL SMASH FRONT AND BACK TERHADAP KEMAMPUAN SMASH OPEN PADA ATLET BOLA VOLI DI KLUB KAE NTT - Anjas Asmara; Johan Irmansyah; Muhsan (Journal Sport Science, Health and Tourism of Mandalika (Jontak) e-ISSN 2722-3116, 2023)
This study aims to determine the effect of front and back smash drill training on the open smash ability of volleyball athletes at the KAE NTT Mataram club in 2023. This research uses a one-group pretest-posttest design. The population of the study consists of 20 volleyball athletes, all of whom were selected using total sampling. The data were collected using a volleyball smash ability test instrument (Nurhasan, 2001), and data analysis was performed using the t-test by comparing the mean scores from pretest and posttest results. The results show that the front smash drill significantly affects the open smash ability, with a t-count of 5.582 > t-table 1.833 at a significance level of 5%. Similarly, the back smash drill also shows significant effects with a t-count of 4.932 > t-table 1.833. The findings suggest that both training methods effectively improve the open smash ability of volleyball athletes. Additionally, there was no significant difference between the two training methods..